State of the art of the evaluation of learning in the modality of e-learning from the perspective of evaluating to learn: conceptual precisions (Revista Electrónica Calidad en la Educación Superior, 2019)
The article presents a state of the art on the subject of evaluating to learn, contextualized under the modality of e-learning, born with the interest of providing a renewed revision of the concept, given the great formative, evaluative and collaborative possibilities offered by the e-learning The article is theoretical in nature and was based on current and academic sources, in order to provide an adequate support to the subject. Among the most important findings are the recognition of the possibilities of e-learning to provide spaces for collaboration and formative feedback to the student body, sometimes even synchronously or in real time, with collaborative work being one of the main axes to promote the Principle of evaluating to learn, without leaving aside the possibility of developing soft skills or generic skills in students.
Keywords: evaluate to learn; distance education; e-learning; ICT; collaborative learning